Erosion rates of 3.5‐cm artificial urinary sphincter cuffs are similar to larger cuffs. (9th August 2018) - McKibben, Maxim J.; Shakir, Nabeel; Fuchs, Joceline S.; Scott, Jeremy M.; Morey, Allen F.
Abstract : Objective: To compare long‐term outcomes and erosion rates of 3.5‐cm artificial urinary sphincter (AUS) cuffs vs larger cuffs amongst men with stress urinary incontinence (SUI), with and without a history of pelvic radiotherapy (RT). Patients and methods: We reviewed the records of all men who underwent AUS placement by a single surgeon between September 2009 and June 2017 at our tertiary urban medical centre. A uniform perineal approach was used to ensure cuff placement around the most proximal corpus spongiosum after precise spongiosal measurement. Patients were stratified by cuff size and RT status, and patient demographics and surgical outcomes were analysed. Cases of AUS revision in which a new cuff was not placed were excluded. Success was defined as patient‐reported pad use of ≤1 pad/day. Results: Amongst 410 cases included in the analysis, the 3.5‐cm cuff was used in 166 (40.5%), whilst 244 (59.5%) received larger cuffs (≥4.0 cm). Over a median follow‐up of 50 months, there was AUS cuff erosion in 44 patients at a rate nearly identical in the 3.5‐cm cuff (10.8%, 18/166) and the ≥4‐cm cuff groups (10.7%, 26/244, P = 0.7). On multivariate logistic regression, clinical factors associated with AUS cuff erosion included a history of pelvic RT, prior AUS cuff erosion, prior urethroplasty, and a history of inflatable penile prosthesis (IPP) placement. Patient demographics were similar between the cuff‐size groups; including age, body mass index, comorbidities, smoking history, RT history, prior AUS, and prior IPP placement. Continence rates were high amongst all AUS patients, with similar success in both groups (82% for 3.5‐cm cuff, 90% for ≥4‐cm cuff, P = 0.1). Conclusions: After 8 years of experience and extended follow‐up, the outcomes of the 3.5‐cm AUS cuff appear to be similar to ≥4‐cm cuffs for effectiveness and rates of urethral erosion. RT patients have a higher risk of cuff erosion regardless of cuff size.